2018
DOI: 10.1111/petr.13268
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo liver resection and autotransplantation with cardiopulmonary bypass for hepatoblastoma in children: A case report

Abstract: Some primary and secondary liver carcinomas cannot be resected using a conventional approach due to their size, location, or major vascular invasion. The aim of this study was to explore the application of ex vivo liver resection and autotransplantation for complicated HB in children. A 1.5-year-old girl with HB after repeated chemotherapy was analyzed. In this patient, tumor invasion includes the IV, V, and VIII liver segments, and thrombosis formed in the inferior vena cava and right atrium. It is difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Vascular reconstruction with extracorporeal circulation is a challenging surgical technique in hepatic resection or LT for HB with tumor thrombi extending into the IVC and RA. To the best of our knowledge, 16 cases of extracorporeal circulation for cases of HB with IVC thrombi or RA (including the present case) have been reported, as shown in Table 1 6,9,12,22‐26 . Hepatic resection was performed under cardiopulmonary bypass with hypothermic perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vascular reconstruction with extracorporeal circulation is a challenging surgical technique in hepatic resection or LT for HB with tumor thrombi extending into the IVC and RA. To the best of our knowledge, 16 cases of extracorporeal circulation for cases of HB with IVC thrombi or RA (including the present case) have been reported, as shown in Table 1 6,9,12,22‐26 . Hepatic resection was performed under cardiopulmonary bypass with hypothermic perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, 16 cases of extracorporeal circulation for cases of HB with IVC thrombi or RA (including the present case) have been reported, as shown in Table 1. 6,9,12,[22][23][24][25][26] Hepatic resection was performed under cardiopulmonary bypass with hypothermic perfusion. Previously, some cases were associated with postoperative mortality or morbidity, such as postoperative death due to pulmonary embolism, 23 and ischemic cholangiopathy requiring subsequent LT. 25 However, recent studies reported that the postoperative course was uneventful and that patients were discharged within a month after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 33 For the unresectable HB, liver transplantation may be effective, with a long-term survival rate of 80% after combination treatment. [34][35][36] Shi et al 37 successfully implemented ex vivo liver resection and autotransplantation for children with HB. The procedure includes removal of the malignancy in vitro or semi-in vivo, transplanting the remaining liver and anastomosing the superior and inferior vena cava, bile duct and other duct systems to restore the liver blood supply.…”
Section: Liver Transplantationmentioning
confidence: 99%